Waris Pengganti sebagai Penyelesaian Waris Islam di Indonesia - Abdul Jamil (Fakultas Hukum Universitas Islam Indonesia, 2003)
Substitute here as orderred in Islam Law compilation as an elaboration from Al-Qur'an verses interpretation on more extensive Islam heir matter. This is also as an resolution for legal controversy in islamic heir principle as part of Islam heir Law in Indonesia.